Processus de marchandisation de la faune sauvage, tensions et conflits dans le parc transfrontalier du Grand Limpopo (parc national Kruger en Afrique du Sud et parc national du Limpopo au Mozambique) - Hugo Mazzero (L'Espace Politique)
In this paper, we analyze the consequences of the co-presence of various stakeholders within the Great Limpopo Transfrontier Park regarding the use of space and resources, in this case wildlife. More specifically, the article focuses on the cooperative links and transboundary relations between Kruger National Park in South Africa and Limpopo National Park in Mozambique, two contiguous national parks that have been the subject of a transboundary conservation process (Great Limpopo Transfrontier Park) since 2002. The aim of this article is to put into perspective the different processes involved in the commodification of wildlife (observation tourism, conservationist mode of production, poaching), and to analyze the extent to which these processes both reveal and amplify tensions and conflicts between the stakeholders present on either side of the border between South Africa and Mozambique. The article follows on from the critical work that has been produced on the Great Limpopo Park, such as Bocchino's and Guyot's research on the influence and domination of South Africa in the process of cross-border cooperation; the work of Andersson et al. and Ferreira on the marginalization of populations living on the edge of parks, or the work of Lunstrum, Duffy et al., Büscher and Ramutsindela on poaching and the militarization of the park. Taking inspiration from Rodary's research on co-presence issues in protected areas, one of the contributions of this article is to integrate the animal question through relationships with wildlife, in order to address socio-economic inequalities and the effects of cross-border conservation policies. We draw on the rich literature of animal geographies, notably Barua's research on lively commodities and encounter value, Brockington and Scholfield's work on conservationist modes of production, Lorrimer and Chanteloup's on wildlife observation tourism and the charismatic dimension of certain animals. After presenting an analysis of the strong contrasts that exist between the national parks studied in terms of development and wildlife density, we propose a typology of stakeholders involved, based on different relationships to wildlife. Finally, the article analyzes the tensions and conflicts arising from the diversity of spatial logics and practices, which question the sustainability of the current transboundary conservation process. One of the contributions of this research is to propose a joint analysis of the dynamics linked to borders and conservation policies, based in particular on empirical data. We draw on data from field surveys carried out in South Africa and Mozambique, among tourists in Kruger National Park (n = 135), local communities in Limpopo National Park (n = 87), and people linked to park management or the conservation sector (n = 15). The results testify to the continuing marked socio-economic contrasts on either side of the border between South Africa and Mozambique. These contrasts are also reflected in the way people relate to wildlife, and remain marked by racialized divisions linked to the history of the parks and the countries.